Alteration in the etiology of penile fracture in the Middle East and Central Asia regions in the last decade; a literature review - Ahmad A Majzoub; Onder Canguven; Talib A Raidh (Urology Annals, 2015)
Penile fracture is a well-recognized, relatively uncommon medical condition and its etiology differs according to geographic area. In this review article, we evaluated literature reported in the past decade, aiming to verify whether there has been any change in the etiology of this condition. A literature review was done for studies published in the past 10 years and focusing on the etiology of penile fracture. Inclusion criteria comprised articles in English language, of sample size more than 10 patients and originating from the Middle East and Central Asia. Data relating to the studied population, etiology of penile fracture, clinical presentation, investigations, management, and outcome was analyzed. One thousand six hundred and twenty-nine patients from 21 original articles were included in the study. The mean age ΁ standard deviation of the patients was 33.3 ΁ 3.23 years. Etiologies of penile fracture were vigorous sexual intercourse, manual bending of erect penis, vigorous masturbation, rolling over in bed and blunt trauma in 41%, 29%, 10%, 14% and 6% patients, respectively. Treatment choices were surgery and conservative, in 1580 (95%), 83 (5%) patients, respectively. A higher incidence of complications was found in conservatively treated patients. As a conclusion, in the last 10 years, vigorous sexual intercourse was the commonest etiology of penile fracture in the Middle East and Central Asia regions. Surgery remains the preferred treatment option for patients diagnosed with penile fracture.